2007
DOI: 10.1038/sj.ijo.0803552
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein B predicts dyslipidemia, metabolic syndrome and, in women, hypertension and diabetes, independent of markers of central obesity and inflammation

Abstract: Objectives: To investigate the role of serum apolipoprotein (apo) B levels in predicting metabolic syndrome (MS), hypertension, atherogenic dyslipidemia and type II diabetes. Methods: Prospective evaluation of 1125 men and 1223 women, aged 28-74 years, participating in the survey 1997/1998 who had serum apo B determinations and were followed-up for a mean 5.9 years. Tertiles of apo B were formed by cut points by 120 and 95 mg/dl. MS was defined by modified ATPIII criteria. Results: Apo B values exhibited no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 23 publications
7
66
1
5
Order By: Relevance
“…According to Onat et al, apolipoprotein B is an indicator of only the level of LDL in the serum. There is no correlation between the protein level and LDL-cholesterol (LDL-C), which could explain the contrasting results of the present study (24) . Further, high levels of triglycerides often alter the correlation between apolipoprotein B level and LDL-C in patients with metabolic syndrome (25) .…”
Section: Resultscontrasting
confidence: 55%
“…According to Onat et al, apolipoprotein B is an indicator of only the level of LDL in the serum. There is no correlation between the protein level and LDL-cholesterol (LDL-C), which could explain the contrasting results of the present study (24) . Further, high levels of triglycerides often alter the correlation between apolipoprotein B level and LDL-C in patients with metabolic syndrome (25) .…”
Section: Resultscontrasting
confidence: 55%
“…However, there may also be nonatherosclerotic compensatory reactions to hypertension like intimal hyperplasia and intimal fibrocellular hypertrophy, which also involve thickening of the arterial wall. 25 In our study, smoking and dyslipidemia were not significantly associated with an increased CAWT. These results were unexpected because they differ from previous publications that have demonstrated an association between active smoking and increased IMT 26,27 and between dyslipidemia and increased IMT.…”
Section: Discussionmentioning
confidence: 62%
“…23,24 The association we observed between increased CAWT and hypertension (P ϭ .0041) may be due to a variety of factors, not necessarily related to atherosclerosis. In fact higher blood pressure and consequent changes in shear stress may cause the transportation of potentially atherogenic particles, 25 which allows the penetration of particles into the arterial wall and consequent plaque formation. However, there may also be nonatherosclerotic compensatory reactions to hypertension like intimal hyperplasia and intimal fibrocellular hypertrophy, which also involve thickening of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…One report demonstrated that apo B was associated with incident type 2 diabetes among Turkish women (7 ). We assessed whether apo B was associated with incident type 2 diabetes and was a better risk predictor than traditional lipid variables in an aboriginal community undergoing rapid cultural transition and with high prevalences of obesity and impaired glucose tolerance (IGT) (8 ).…”
mentioning
confidence: 99%